Double Sequence Space of Fuzzy Real numbers Defined by Double Orlicz Function - Hussein Battor, Ali; Fawzidabbas, Alaa; Azeen Neamah, Maysoon (International Journal of Psychosocial Rehabilitation, 2020)
Through this paper, we introduce some double sequence space of fuzzy real numbers defined by a double Orlicz function. We study some of their features, such as solidity, symmetry, completeness, etc., and prove some important results.